Moderating effects of decision autonomy and culture novelty on the relationship between expatriate manager leadership styles and host country managers' job satisfaction: Evidence from the global hotel industry. (August 2021) - Takeuchi, Riki; Qian, Cuili; Chen, Jieying; Shay, Jeffrey P
While the use of expatriate managers to control and manage the foreign subsidiary is well recognized, there is a paucity of literature that considers how expatriate managers' leadership behaviors affect host country nationals (HCNs). By incorporating leadership contingency perspective into expatriation literature, we examine the boundary conditions of two leadership (planning and consulting) behaviors on HCN managers' job attitude (i.e., job satisfaction). Specifically, we investigate the moderating effects of decision autonomy and culture novelty of expatriate managers on the aforementioned relationships, using survey data collected from 103 expatriate general managers and 276 HCN managers working in nine American-based multinational hotel chains and found both planning and consulting leadership behaviors to be positively related to HCN managers' job satisfaction. Decision autonomy and culture novelty acted as boundary conditions of such relationships such that decision autonomy moderated the planning-job satisfaction relationship while culture novelty moderated the consulting-job satisfaction relationship.